First we will use both triangles to make one to find what x is for example:
angle 1: 42
angle 2: 55 + 26 = 81
angle 3: x = 180 - (angle 1 + angle 2) = 180 - 123 = 57
Now that we know what x is we can find what y is for example:
angle 1: 26
angle 2: x = 57
angle 3: y = 180 - (26 + 57) = 180 - 83 = 97
Now that we know what y is we can find what z equals knowing they are on a straight line which means that they both equal 180 degrees when they add up for example:
z = 180 - 97 = 83
Now that we know all of our variables we can check it by adding up the angles of the 3 triangles for example:
triangle 1: 81 + 42 + 57 = 180
triangle 2: 26 + 57 + 97 = 180
triangle 3: 55 + 42 + 83 = 180
So z = 83 and y = 97 and x = 57, Hope this helps a lot ^^